PENATALAKSANAAN FISIOTERAPI PADA CARPAL TUNNEL SYNDROME DENGAN ULTRASOUND THERAPY DAN STRETCHING EXERCISE - Laki, Alexander; Sumarsono (Fakultas Keperawatan, Universitas Katolik De La Salle Manado, 2023)
Introduction: Carpal Tunnel Syndrome (CTS) is the collection of symptoms and signs associated with median neuropathy at the carpal tunnel. Wrist pain is the main symptom of carpal tunnel syndrome. Sometimes the pain radiates to the upper arm, at the night the pain gets worse so that the patient has trouble sleeping. Numbness and tingling in the thumb, index finger, middle finger and the thumb side of the ring finger. Objective: This case study aims to determine the physiotherapy management in cases of carpal tunnel syndrome with ultrasound and stretching exercise. The respondent in this case study is a 51-year-old at Sam Ratulangi Tondano Hospital. Assessment of pain using the Visual Analog Scale (VAS) and functional activities with the Wrist Hand Disability Index (WHDI). After doing the therapy 6 times. Result: The results obtained by giving ultrasound and strecthing exercise are as follows, for pain examination, tenderness from 2,8 decrease to 2 and motion pain from 4 decrease to 2,9 and for functional activity experienced an increase in functional activity, with the result from 32 % moderate disability to 8 % minimal disabilty. Conclusion: The conclusion in this case study is that ultrasound and stretching exercise can reduce pain and increase functional activity in carpal tunnel syndrome.